Tolerance of Senecavirus A to Mutations in Its Kissing-Loop or Pseudoknot Structure Computationally Predicted in 3′ Untranslated Region - Liu, Fuxiao; Zhao, Di; Wang, Ning; Li, Ziwei; Dong, Yaqin; Liu, Shuang; Zhang, Feng; Cui, Jin; Meng, Hailan; Ni, Bo; Wei, Rong; Shan, Hu (Frontiers in Microbiology, 2022)
Senecavirus A (SVA) is an emerging virus that belongs to the genus Senecavirus in the family Picornaviridae. Its genome is a positive-sense and single-stranded RNA, containing two untranslated regions (UTRs). The 68-nt-long 3' UTR is computationally predicted to possess two higher-order RNA structures: a kissing-loop interaction and an H-type-like pseudoknot, both of which, however, cannot coexist in the 3' UTR. In this study, we constructed seventeen full-length SVA cDNA clones (cD-1 to -17): the cD-1 to -7 contained different point mutations in a kissing-loop-forming motif (KLFM); the cD-8 to -17 harbored one single or multiple point mutations in a pseudoknot-forming motif (PFM). These seventeen mutated cDNA clones were independently transfected into BSR-T7/5 cells for rescuing recombinant SVAs (rSVAs), named rSVA-1 to -17, corresponding to cD-1 to -17. The results showed that the rSVA-1, -2, -3, -4, -5, -6, -7, -9, -13 and -15 were successfully rescued from their individual cDNA clones. Moreover, all mutated motifs were genetically stable during ten viral passages in vitro. This study unveiled viral abilities of tolerating mutations in the computationally predicted KLFM or PFMs. It can be concluded that the putative kissing-loop structure, even if present in the 3′ UTR, is unnecessary for SVA replication. Alternatively, if the pseudoknot formation potentially occurs in the 3′ UTR, its deformation would have a lethal effect on SVA propagation.